Students’ Perceptions and the Implications of Cross-Cultural Awareness in German Language Learning at Universitas Negeri Malang - Bestyana, Yuvita Dwi Agnie; Usman, Rizman; Suyono, Suyono (Journal of Educational Sciences, 2025)
This study investigates students’ perceptions of German culture and the implications of cross-cultural awareness in learning German at Universitas Negeri Malang. A mixed-methods design was applied, involving questionnaires completed by 82 students and interviews with 10 participants. The results show that students generally hold positive perceptions of German culture, with more than 70% acknowledging that cultural awareness is essential for language learning. They expressed strong interest in German cuisine, traditions, and the opportunity to visit Germany, while 62.2% emphasized the role of digital media in providing access to cultural knowledge. The interview findings reinforce the quantitative data, revealing that cultural learning increased motivation and encouraged students to reflect on their own cultural identity. Students reported that exposure to German punctuality, discipline, and communication styles enhanced their intercultural understanding and broadened their perspectives. Cultural awareness was also perceived to enrich knowledge, foster tolerance, and strengthen intercultural communicative competence. Moreover, the inclusion of cultural elements in teaching materials and the involvement of native speakers were seen as highly motivational. In conclusion, the study highlights the importance of integrating culture into German language education. Such integration supports both linguistic proficiency and intercultural competence, preparing students to engage effectively in diverse cultural contexts.